2020
DOI: 10.1108/jhtt-03-2019-0049
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing Generation Y’s tourism-related social media activity: the case of Polish students

Abstract: Purpose This study aims to identify the factors which affect Generation Y’s activity in social media (SM) while traveling. It draws on and extends the technology acceptance model (TAM) and social influence theory. It examines the effects of social influence processes (compliance, identification and internalization), perceived enjoyment (PE), perceived risk, perceived ease of use and perceived usefulness on tourism-related SM activity. Design/methodology/approach The study tested the model with a sample of 42… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…Recently, Kowalczyk-Anioł and Nowacki [75] have concluded that the variable perceived enjoyment is important for younger generations. This paper has not considered intergenerational differences.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…Recently, Kowalczyk-Anioł and Nowacki [75] have concluded that the variable perceived enjoyment is important for younger generations. This paper has not considered intergenerational differences.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…For example, for the variable relationship between perceived usefulness and adoption intention for a hotel mobile app, Huang et al (2019) confirmed that the correlation is small, while the study by Kim (2016) showed that the correlation is very large. For the use of social media in the process of tourism decision-making, Kowalczyk-Anio and Nowacki (2020) confirmed that the correlation between perceived usefulness and adoption intention is small, while Mariani et al (2019) argued that the correlation is very large. Through meta-analysis, this study found that the above conclusions are also applicable to online travel service situations, and the correlation coefficients refer to ATTD-AI, PEOU-AI, PU-AI, PEOU-ATTD, PU-ATTD and PEOU-PU relationships, which are large and consistent with many studies on online travel services (Salehi-Esfahani and Kang, 2019; Bae and Han, 2020).…”
Section: Discussionmentioning
confidence: 90%
“…Generally speaking, online travel services include booking travel products through travel websites, online travel communities or mobile travel apps (Hua et al , 2021); obtaining travel information; and making travel decisions through online communities, non-travel-specific social media, or tourism-related social media (Kowalczyk-Anio and Nowacki, 2020; Zhang et al , 2020; Mirzaalian and Halpenny, 2019), as well as specific tourism information systems (IS) such as intelligent travel assistant, mobile augmented reality apps, location-based services and biometric technology in hotels (Do et al , 2020; Phaosathianphan and Leelasantitham, 2019; Shin and Jeong, 2021). In the online travel service context, some issues related to users’ adoption behaviors and intentions have attracted much attention, and adoption behaviors refer to how individuals actually use online travel services within a certain period of time, while adoption intention refers to the intensity of individuals’ willingness to use online travel services in the future (Javed et al , 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Their childhood and youth coincide with globalization and universal, everyday access to the Internet. They instinctively turn first to the Internet to communicate, understand, learn, and find, and they constantly update online content [ 50 , 51 ]. They also frequently use mobile services, treating them as a medium of self-expression [ 46 ].…”
Section: Literature Reviewmentioning
confidence: 99%